Perbandingan Efek Jus Buah Pare (Momordica charanti L), Jus Biji Petai (Parkia speciosa Hassk) Dan Kombinasi Keduanya Terhadap Kadar HDL (High Density Lipoprotein) Dan Kadar LDL (Low Density Lipoprotein) Darah Tikus Putih Jantan (Rattus Norvegicus) Galur - andestya nanda pratama; Syazili Mustofa; Tri Umiana Soleha (CV. Jasa Sukses Abadi, 2022)
Background: Dyslipidemia is an abnormality of lipid fraction in blood plasma, Dyslipidemia can cause coronary heart disease (CHD) which is the main cause of death in the world. Bitter melon juice (Momordica charanti L), bitter beans juice (Parkia speciosa Hassk) has an antioxidant (antidislipidemia) that able to influence the LDL and HDL level. Purpose: Compare Bitter melon Fruit Juice, bitter beans Juice and the combination of HDL and LDL levels in male white rats with a high-fat diet. Method: An experimental study using a posttest control only design group. Using 30 white Wistar rats. There were 5 groups, there are the negative control group (K-) were only given a standard diet, 4 other controls were given a high-fat diet, the positive control group (K+) were only given 2ml/200gBB quail egg yolk, bitter melon (P1) 100ml/KgBB , bitter beans juice (P2) 100ml/KgBB/day, and combination juice (P3) 200ml/KgBB, for 14 days. Results: Average HDL levels in bitter melon juice group (78.73 ± 1.42 mg/dl), bitter beans juice group (65.74 ± 2.02 mg/dl), and combination juice group (70.37 ± 1.35mg/dl). The mean LDL level in the bitter melon fruit juice group (75.92 ± 1.28 mg/dl), bitter beans juice group (76.52 ± 1.20 mg/dl), and combination juice group (52.12 ± 1.20 mg/dl). The mean HDL and LDL levels in treatment groups were significantly different from negative (K-) and positive (K+) control groups with p <0.05 Conclusion: Giving fruit juice is better than HDL levels, and combination juice is better for LDL levels in male white rats on a high-fat diet.